Moral construction strategy in pesantren Al-Musyahadah through sharing session programme - Sophia, Ratna; Maulana, Muhammad Fanza; Maryanah, Vika; Haeruman, Riziq; Kosim, Abdul (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
Islamic boarding schools are one of the educational institutions that are effective in conducting moral development because of the coaching factors and the supportive environment. Pesantren has an important role in the process of moral development in someone, especially students. The purpose of this study is to find out moral development in Al-Musyahadah Islamic Boarding School, especially in the field of Sharing Session which is a special strategy in fostering the morals of its students. This research uses qualitative research with a case study approach. Where this research focuses on boards, administrators and students who are directly involved in moral development. Data collection techniques in this study are using in-depth interview techniques, direct observation and surveys as well as documentation. To check the validity of this paper, data triangulation is carried out, namely inter-researcher triangulation, source triangulation and method triangulation. For data analysis, data reduction, data display and conclusion drawing were carried out which resulted in a study, namely about moral development at Al-Musyahadah Islamic Boarding School and also moral development strategies through Sharing Sessions at Al-Musyahadah Islamic Boarding School. The results of this study show that there are several types of moral development carried out at the Al-Musyahadah Islamic Boarding School, such as the Sharing Session, Meeting Night and discussion in addition, the most effective moral development strategy at the Al-Musyahadah Islamic Boarding School is the Sharing Session.Â Pondok pesantren merupakan salah satu lembaga pendidikan yang efektif dalam melakukan pengembangan moral karena faktor pembinaan dan lingkungan yang mendukung. Pesantren memiliki peran penting dalam proses perkembangan moral dalam diri seseorang, khususnya pelajar. Tujuan penelitian ini adalah untuk mengetahui perkembangan moral di Pondok Pesantren Al-Musyahadah, khususnya di bidang Sharing Session yang merupakan strategi khusus dalam membina akhlak para santrinya. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan studi kasus. Dimana penelitian ini berfokus pada dewan, administrator dan mahasiswa yang terlibat langsung dalam pengembangan moral. Teknik pengumpulan data dalam penelitian ini menggunakan teknik wawancara mendalam, observasi langsung dan survei serta dokumentasi. Untuk memeriksa keabsahan makalah ini, dilakukan triangulasi data yaitu triangulasi antar peneliti, triangulasi sumber dan triangulasi metode. Untuk analisis data dilakukan reduksi data, tampilan data dan penarikan kesimpulan yang menghasilkan kajian yaitu tentang perkembangan moral di Pondok Pesantren Al-Musyahadah dan juga strategi pengembangan moral melalui Sharing Session di Pondok Pesantren Al-Musyahadah. Hasil penelitian ini menunjukkan bahwa ada beberapa jenis perkembanganÂ  moral yang dilakukan di Pondok Pesantren Al-Musyahadah, seperti Sharing Session, Meeting Night dan diskusi selain itu, strategi pengembangan moral yang paling efektif di Pondok Pesantren Al-Musyahadah adalah Sharing Session.Â